Drosophila TRP and TRPL are assembled as homomultimeric channels in vivo - Katz, Ben (The Company of Biologists, 2013)
Family members of the cationic transient receptor potential (TRP) channels serve as sensors and transducers of environmental stimuli. The ability of different TRP channel isoforms of specific subfamilies to form heteromultimers and the structural requirements for channel assembly are still unresolved. Although heteromultimerization of different mammalian TRP channels within single subfamilies has been described, even within a subfamily (such as TRPC) not all members co-assemble with each other. In Drosophila photoreceptors two TRPC channels, TRP and TRP-like protein (TRPL) are expressed together in photoreceptors where they generate the light-induced current. The formation of functional TRP–TRPL heteromultimers in cell culture and in vitro has been reported. However, functional in vivo assays have shown that each channel functions independently of the other. Therefore, the issue of whether TRP and TRPL form heteromultimers in vivo is still unclear. In the present study we investigated the ability of TRP and TRPL to form heteromultimers, and the structural requirements for channel assembly, by studying assembly of GFP-tagged TRP and TRPL channels and chimeric TRP and TRPL channels, in vivo. Interaction studies of tagged and native channels as well as native and chimeric TRP–TRPL channels using co-immunoprecipitation, immunocytochemistry and electrophysiology, critically tested the ability of TRP and TRPL to interact. We found that TRP and TRPL assemble exclusively as homomultimeric channels in their native environment. The above analyses revealed that the transmembrane regions of TRP and TRPL do not determine assemble specificity of these channels. However, the C-terminal regions of both TRP and TRPL predominantly specify the assembly of homomeric TRP and TRPL channels.